Stress levels and quality of sleep in subjects with temporomandibular joint dysfunction - Martins, Ronald Jefferson [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Garcia, Alício Rosalino [UNESP]; Garbin, Artênio José Isper [UNESP]; Miguel, Natália [UNESP] (FapUNIFESP (SciELO), 2010)
Purpose: The aim of this study was to test the association between quality of sleep and stress in individuals with temporomandibular disorder (TMD). Methods: The study sample consisted of 354 adult subjects (males and females) from the municipality of Piacatu, São Paulo state, in the Southeast region of Brazil. Data were collected using the Fonseca’s Questionnaire to record the level of TMD, the Pittsburgh Sleep Quality Index (PSQI) to assess quality of sleep and the Social Readjustment Rating Scale (SRRS) to record stress level. The data were analyzed by the software Epi Info 2000 version 3.2 using a chi-square test at the 0.05 level of significance. Results: One hundred and eighty (50.8%) subjects had some level of TMD. The statistical analysis showed a significant relationship between the three stress scores and the presence or absence of sleep disorders, considering an overall PSQI score > 5 as an indicator of a subject with sleep problems (P<0.01). Conclusion: Both quality of sleep and stress levels were associated with TMD in this sample.

Objetivo: O objetivo deste trabalho foi comparar níveis de estresse e qualidade do sono em indivíduos com DTM. Metodologia: O universo desta pesquisa constituiu-se por 354 indivíduos de ambos os sexos do município de Piacatu, SP, Brasil. Os dados foram coletados através do uso de: Questionário de Fonseca para verificar o grau de DTM, Índice da Qualidade do Sono de Pittsburgh (PSQI) para a qualidade do sono e a Escala de Reajustamento Social (SRRS) para o grau de estresse. Os dados foram tabulados por meio do programa Epi Info 2000, versão 3.2, e analisados estatisticamente por meio do Teste Qui-Quadrado, ao nível de significância de 5%. Resultados: Do total, 180 (50,8%) apresentavam algum grau de disfunção temporomandibular, sendo que destes, 96 (53,3%) tinham distúrbios do sono e 107 (59,4%) graus mais elevados de estresse. O teste estatístico mostrou relação entre os fatores analisados (P<0,01). Conclusão: Há associação estatisticamente significativa entre qualidade do sono e estresse em indivíduos com DTM.
Níveis de estresse e distúrbios do sono em indivíduos com disfunção temporomandibular
Keywords: Temporomandibular joint; Temporomandibular joint dysfunction syndrome; Sleep disorders; Stress; Articulação temporomandibular; Síndrome da disfunção da articulação temporomandibular; Transtornos do sono; Estresse